Dopaminergic mechanisms supporting hippocampal postencoding dynamics in humans - Claire J. Ciampa; Thomas M. Morin; Jourdan H. Parent; Alex Adornato; Jordyn L. Cowan; Katherine O’Malley; Rachel E. Marcus; Charlee Gordon; James D. Howard; Arielle Tambini; Cristina Cusin; Jacob Hooker; et al. (Proceedings of the National Academy of Sciences, 2026)
Deficits in dopamine function cause alterations in episodic memory. Converging evidence implicates dopamine in postencoding hippocampal mechanisms inferred to support long-term memory, though there is a lack of direct evidence in humans. We address this gap using pharmacological functional MRI (fMRI) and positron emission tomography (PET). Using a motivated reward encoding task on and off oral methylphenidate, we tested whether individual differences in baseline dopamine ([ 11 C]raclopride PET D2/3 receptor density) relate to drug-induced changes in hippocampal postencoding processes. Our study focused on healthy older adults, who are among those most vulnerable to memory decline and may benefit from pharmacologically enhancing dopamine. We found that methylphenidate administration was associated with improved memory performance relative to placebo for both high and low reward conditions. Older adults with high receptor density showed greater persistence of hippocampal multivoxel patterns into postencoding rest and stronger hippocampus-midbrain resting-state connectivity following encoding while on methylphenidate. These findings support the view that enhanced dopaminergic tone, verified through PET, directly modulates hippocampal postencoding dynamics in humans. Substantial variation in neurobiological effects was associated with individual differences in baseline dopamine function as older adults with high dopamine receptor density profiles showed preferential benefit of drug on hippocampal function, though these insights are qualified by null associations between memory performance and postencoding hippocampal activity. Individuals with lower dopamine receptor profiles showed preferential benefit of reward incentives suggesting altered sensitivity to extrinsic motivational factors depending on endogenous dopamine function.